Design of a labVIEW system applied to predictive maintenance - Mathias, Mauro Hugo [UNESP]; De Medeiros, Everton Coelho [UNESP]; Gonçalves, Valdeci Donizete [UNESP] (Trans Tech Publications, 2013)
The implementation of vibration analysis techniques based on virtual instrumentation has spread increasingly in the academic and industrial branch, since the use of any software for this type of analysis brings good results at low cost. Among the existing software for programming and creation of virtual instruments, the LabVIEW was chosen for this project. This software has good interface with the method of graphical programming. In this project, it was developed a system of rotating machine condition monitoring. This monitoring system is applied in a test stand, simulating large scale applications, such as in hydroelectric, nuclear and oil exploration companies. It was initially used a test stand, where an instrumentation for data acquisition was inserted, composed of accelerometers and inductive proximity sensors. The data collection system was structured on the basis of an NI 6008 A/D converter of National Instruments. An electronic circuit command was developed through the A/D converter for a remote firing of the test stand. The equipment monitoring is performed through the data collected from the sensors. The vibration signals collected by accelerometers are processed in the time domain and frequency. Also, proximity probes were used for the axis orbit evaluation and an inductive sensor for the rotation and trigger measurement. © (2013) Trans Tech Publications, Switzerland.
Keywords: Condition monitoring; Graphical programming language; LabVIEW; Predictive maintenance; A/D converter; Data collection system; Equipment monitoring; Graphical programming; Industrial branches; LabViEW; Large-scale applications; Low costs; Monitoring system; National Instruments; Oil exploration; Rotating machine; Test stands; Time domain; Vibration analysis techniques; Vibration signal; Virtual instrument; Virtual Instrumentation; Accelerometers; Automobile engines; Computer graphics; Inductive sensors; Maintenance; Mechanical engineering; Vibration analysis; Computer programming languages